PERBANDINGAN EFEKTIVITAS JUS BUAH TOMAT (LYCOPERSICUM ESCULANTUM MILL.) DENGAN JUS BUAH JAMBU BIJI MERAH (PSIDIUM GUAJAVA L.) TERHADAP PENURUNAN KADAR KOLESTEROL TOTAL PADA TIKUS PUTIH JANTAN YANG DIINDUKSI KUNING TELUR - MUHAMMAD AULIA RAHMAN; IRFAN HAMDANI; ISRA THRISTY; MUHAMMAD JALALUDDIN ASSUYUTHI CHALIL (JURNAL ILMIAH SIMANTEK, 2019)
Communities have an unhealthy lifestyle that leads to an increase in total cholesterol levels. Tomato juice (Lycopersacum esculentum M.) and red guava (Psidium guajava L.) contain lycopene which is high enough of antioxidant that can lower blood cholesterol levels. Methods: This study was experimental using pretest posttest with control group design. White rat (Rattus norvegicus L.) male 24 wistar strain induced egg yolk 6.25gr / kgBW, grouped into 4, negative controls were given distilled water, positive control was given egg yolk, one treatment was given tomato juice 3 cc and two treatment was administered 3 cc red guava fruit juice for 2 weeks then blood was taking for 3 times, pretest, intervention and posttest. Result: the average of total cholesterol level posttest negative control group, positive control, one treatment and two treatment respectively 64,82 mg / dl, 78,48 mg / dl, 61,24 mg / dl, 41,81 mg / dl . ANOVA test results showed that there was a significant difference between posttest intervention of treatment group one and treatment group two with p = 0,021 and 0,000 (p <0,05). Conclusion: The provision of tomato juice and red guava juice can reduce total cholesterol levels of rats. Red Guava juice is more effective to lower total cholesterol of rats.